Pengaruh Pengetahuan terhadap Kemampuan Cuci Tangan Keluarga Pasien dalam Mencegah Infeksi Nosokomial di RS Bhakti Asih Tangerang 2024 - Nurul Khotimah; Ayu My Lestari Saragih; Siti Nurbaiti; Ns. Dwi Retno Handayani; Nurdewi Sulymbona (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Knowledge is the result of a person's knowledge of objects through their senses, namely the sense of hearing, sense of smell, sense of sight, sense of smell, and sense of touch. Ability is an individual's capacity to perform various tasks in a job. Hand washing is the activity of cleaning hands by rubbing and using soap and rinsing it in running water. The purpose of the study was to identify the relationship between the level of knowledge and the ability to wash hands in the families of patients regarding nosocomial infections in the inpatient room of Nusa Indah Bhakti Asih General Hospital, Tangerang. The research method uses the chi square test with the sampling technique used in this study is Non Random Sampling (Non Probability Sampling) which is carried out by Purposive Sampling technique. The instruments used in this study are the questionnaires used in this study, including knowledge of hand washing and handwashing ability sheet. Data analyzed This study uses the Chi square test for categorical data that is said to be related if p < 0.05. The results of the study showed that the P Value was 0.000, where the P Value was smaller than alpha (0.05), then H0 was rejected, meaning that knowledge was significantly related to the ability to wash hands in the patient's family regarding nosocomial infections in the Nusa Indah Inpatient Room, Bhakti Asih General Hospital, Tangerang City in 2024. In conclusion, there is a relationship between the level of knowledge and the ability to wash hands in the patient's family.